Pluralities 1980 - Fry, Philip; Holmes, Willard; MacKay, Allan; Pontbriand, Chantal; Bradley, Jessica (Ottawa : National Gallery of Canada, 1980)
Baden, Mowry ; Baxter, Iain ; Boogaerts, Pierre ; Brener, Roland ; Cruise, Stephen ; Dean, Max ; Fafard, Joe ; General Idea ; Goodwin, Betty ; Kennedy, Garry Neill ; McEwen, John ; Mongrain, Claude ; Poulin, Roland ; Proch, Don ; Racine, Rober ; Thauberger, David ; Wall, Jeff ; Westerlund, Mia ; Wyse, Alex
Pluralities 1980 Pluralités, The National Gallery of Canada, Ottawa, 1980
boek